Science and technology of polymers and advanced materials : applied research methods - Mukbaniani, O. V.; Tatrishvili, Tamara; Abadie, Marc J. M. (Apple Academic Press Inc., 2020)
"Increasing interest in lightweight and high-performance materials is leading to significant research activity in the area of polymers and composites. One recent focus is to develop multifunctional materials that have more than one property tailored as to the specified design requirements, in addition to achieving low density. The possibility of simultaneously tailoring several desired properties is attractive but very challenging, and it requires significant advancement in the science and technology of high-performance functional polymers and composites. This volume, Science and Technology of Polymers and Advanced Materials: Applied Research Methods, presents a selection of new approaches in the field of composites and nanomaterials, polymer synthesis and applications, and materials and their properties. Some composites/nanocomposites and interfaces are explored as well, some with medical applications. The authors also look at simulations and modeling, synthesis involving photochemistry, self-assembled hydrogels, and sol-gel processing. Part I reviews research on several nanoparticles to reinforce polymer matrices, thermoplastics, and thermosets. Diverse composite-based epoxy, polyester, ethylene/propylene, polyethylene, PMMA, even natural polymers are presented for different type of applications, and interfaces/interphases for reinforcing composites and nanocomposites are considered as well. Special attention is brought to medical applications, such as tissue engineering, prostate cancer biomarkers, and dealing with nanomedicine. Part II explores some new syntheses by using classical techniques and photochemistry for different applications, such as health care cosmetics, waterproofing materials, sorbents for different nature ions sorption, and antibacterial activity. Part III goes on to discuss hydrogels, intergel systems, sol-gels, and zeolithes. This book presents interdisciplinary papers on the state of knowledge of these topics through a combination of overviews and original unpublished research. The information found here will be valuable to those working in the field of polymers and composites, including academics, institutes, research centers, as well as engineers working in the industry."- Resumé vydavatel